2000
DOI: 10.1021/bi0020574
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine 123 Binds to Multiple Sites in the Multidrug Resistance Protein (MRP1)

Abstract: The mechanisms of MRP1-drug binding and transport are not clear. In this study, we have characterized the interaction between MRP1 and rhodamine 123 (Rh123) using the photoreactive-iodinated analogue, [(125)I]iodoaryl azido-rhodamine 123 (or IAARh123). Photoaffinity labeling of plasma membranes from HeLa cells transfected with MRP1 cDNA (HeLa-MRP1) with IAARh123 shows the photolabeling of a 190 kDa polypeptide not labeled in HeLa cells transfected with the vector alone. Immunoprecipitation of a 190 kDa photola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 45 publications
3
81
0
Order By: Relevance
“…5b), which indicated background transport of the probe. It is possible that this additional efflux may be mediated by the Multidrug Resistance Protein-1 (MRP-1), which has been reported to also transport this dye (31). These observations support the fact that Rho 123 efflux assay is a poorly selective method to assess low levels of P-gp activity and shall be replaced by a more selective method like UIC2 shift assay.…”
Section: Discussionmentioning
confidence: 81%
“…5b), which indicated background transport of the probe. It is possible that this additional efflux may be mediated by the Multidrug Resistance Protein-1 (MRP-1), which has been reported to also transport this dye (31). These observations support the fact that Rho 123 efflux assay is a poorly selective method to assess low levels of P-gp activity and shall be replaced by a more selective method like UIC2 shift assay.…”
Section: Discussionmentioning
confidence: 81%
“…Photolabeling studies of MRP1 using azido derivatives of IACI and IAARh123 followed by partial proteolysis have identified two preferential sites of cross-linking involving peptides containing TM helices 10 and 11 or TM 16 and 17 (31)(32)(33). Our previous photolabeling studies of MRP1 have shown that LTC 4 , like IACI and IAARh123, labels sites in MSD2 and MSD3 (27).…”
Section: Discussionmentioning
confidence: 95%
“…As an alternative approach to identifying regions of the protein directly involved in substrate binding, MRP1 has been photolabeled by its known high affinity physiological substrate LTC 4 as well as by compounds that are less well characterized with respect to binding and transport (10,12,27,(31)(32)(33)(34). Although these compounds compete with LTC 4 for binding to MRP1, their affinities appear to be considerably lower, and they also interact with the distantly related P-glycoprotein.…”
Section: Multidrug Resistance Protein 1 (Mrp1/abcc1)mentioning
confidence: 99%
See 1 more Smart Citation
“…So far none of them has been described as a substrate specific for P-gp. Rh 123 is a P-gp substrate, but its also a MRP1 and BCRP substrate (18,19), and Ca-AM is a P-gp and MRP substrate (12). Until now, JC-1 and Syto 16 haven't been described as either a MRP or a BCRP substrate.…”
Section: Discussionmentioning
confidence: 99%